Construction and implement of hierarchical management system for specialist nurses based on Patricia Benner’s theory - Yu, Haiyan; Chen, Yuan; Wu, Linjing; Wang, Ligang; Lai, Yuting; You, Aijun (Frontiers in Medicine, 2024)
Objective To construct a hierarchical management system for specialist nurses based on Patricia Benner's theory, and evaluate its implement effect, so as to provide reference for the hierarchical management of specialist nurses.Methods Literature retrieval, semi-structured interview and Delphi method were conducted for initially formulation of the draft of hierarchical management system for specialist nurses. 43 specialist nurses and 14 nursing managers were selected for the study, using a non-randomized controlled experimental study design, and at the end of the study, the job satisfaction, job engagement, job exuberance, advice behaviors and nursing managers' overall job satisfaction of specialist nurses were compared before and after the hierarchical management.This study constructed a hierarchical management system for specialist nurses. The differences in specialist nurses' job satisfaction, job engagement, job exuberance and constructive behaviors before and after hierarchical management were statistically significant (P<0.05), and the differences in the nursing managers' assessment of specialist nurses' overall job satisfaction were statistically significant (P<0.05).The hierarchical management system of specialist nurses based on Patricia Benner's theory improves the quality of hierarchical management of specialist nurses, which could improve the job satisfaction of specialist nurses. The system could provide guidance and reference for hierarchical management system of specialist nurses.